Making Green Schools a Reality through Economically Sustainable Strategies - Meenal Arora (Journal of Education for Sustainable Development Studies, 2025)
The imperative to “learn to live sustainably” is widely recognized, yet environmental concerns remain marginal within mainstream educational systems across the globe. Education, as identified by UNESCO, is both a foundational pillar of sustainable development and its principal enabler, capable of shaping attitudes and competencies necessary for effective climate action and resource management (UNESCO, 2024). Green Schools exemplify this integration by employing a whole-institution approach to embed sustainability within teaching, operations, governance, and community engagement, empowering learners and all school stakeholders to address complex social, economic, and environmental challenges. This study aims to guide policymakers, school administrators, and education managers in adopting economically sustainable strategies for the realization of Green Schools. The research employed a qualitative methodology, combining systematic literature review of academic publications, policy reports, and institutional case studies discussing the environmental, social, and economic dimensions of sustainable schooling. To enhance contextual relevance, the study also incorporated case studies of schools in India that have successfully implemented green initiatives, using semi-structured interviews and surveys with administrators, teachers, and students to capture firsthand experiences and perceptions. Key findings indicate that the sustainable transformation of schools is facilitated by four core strategies: developing multi-sector partnerships, reinvesting operational cost savings, leveraging strengths-based models to integrate sustainability across disciplines, and employing cost-effective technologies that reduce environmental footprints while fostering financial resilience. Notably, case examples illustrate how these strategies—when adopted collectively—embed environmental responsibility throughout school governance, operations, curriculum, and community relationships. The study concludes that actionable, economically sustainable models empower all members of the school community, from leadership to learners, to participate actively in advancing Education for Sustainable Development (ESD) goals. By presenting replicable best practices and mechanisms for continuous improvement, this research contributes practical insights for schools worldwide seeking to align their educational environments with global sustainability objectives.